Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan (Studi Kasus pada Pengguna Aplikasi Belanja Online Tokokota) - Eva Dolorosa; Fany Depita Julianti; Anita Suharyani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aimed to empirically investigate the relationship between service quality and customer loyalty within the context of Tokokota's online platform in Pontianak. The research was conducted in Pontianak City with 150 respondents. Employing quantitative and qualitative data collection methods and leveraging structural equation modeling for analysis, the study identified key service quality dimensions (such as ease of use, information completeness, and product variety) that significantly influence customer loyalty. Employing a mix of surveys and interviews and analyzing the data with SEM, the study concluded that service quality greatly affected customer loyalty and highlighted specific service aspects that require improvement to increase loyalty. The findings provide valuable insights for Tokokota in formulating strategies to optimize service quality and enhance customer retention. Service quality is analyzed through indicators of ease of use, appearance, reliability, communication, and incentives.